2017
DOI: 10.1177/1464420716675507
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress analysis of one- and two-dimensional functionally graded plates subjected to in-plane heat fluxes

Abstract: This study addresses the thermal stress analysis of one- and two-dimensional functionally graded plates subjected to in-plane heat fluxes. The material composition variation is assumed in-plane, not through the plate thickness according to a power-law distribution in terms of the volume fraction of the constituents. The mathematical model considers the spatial derivatives of local mechanical and thermal properties. The heat transfer and Navier equations of the two-dimensional thermo-elastic model were discreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Central difference formulae are adopted for position derivative and backward difference formulae are implemented for time derivative. To evaluate the temperature fields, the equal number of nodal points with the equal mesh size are considered like equation (6). So, the size of each mesh is, Δr = (b−a)/(N-1).…”
Section: Solution Of Heat Conduction Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Central difference formulae are adopted for position derivative and backward difference formulae are implemented for time derivative. To evaluate the temperature fields, the equal number of nodal points with the equal mesh size are considered like equation (6). So, the size of each mesh is, Δr = (b−a)/(N-1).…”
Section: Solution Of Heat Conduction Equationsmentioning
confidence: 99%
“…Analysis of various structural components of functionally graded materials is quite extensive in literature. 110…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first aspect in this part is the dimensionality of FGP, which refers to the number of dimensions through which properties variation occurs. Composition variation happens through the thickness, or the in-plane two dimensions [51,52] as shown in Fig. 3.…”
Section: Fgp's Fgm Characteristicsmentioning
confidence: 99%
“…Generally, in FGM structures ceramics material is used with another material to withstand high temperature, corrosion, wear, and adverse environmental effect while maintaining their structural integrity. A number of studies have shown the viability of FGM structures in multiphysics problems involving beam, 10 plate, [11][12][13][14] shell, 15 pressure vessels. 16 In recent years, many studies have been conducted on the thermo-elastic field and magneto-thermo-elastic fields of circular disk which have extensively been used in many engineering components including grinding wheel, circular saw, high-speed gears, flywheel, gas turbine rotor, etc.…”
Section: Introductionmentioning
confidence: 99%